Your complete guide to a successful & secure retirement : the definitive resource for anyone planning retirement - Swedroe, Larry E. (Hampshire, Great Britain : Harriman House Ltd, 2021)
"This is your one-stop, definitive resource as you prepare for a secure and comfortable retirement. Investment and personal finance experts Larry Swedroe and Kevin Grogan present uniquely comprehensive coverage of every important aspect you need to think about as you approach retirement, including: Social Security, Medicare, investment planning strategy, portfolio maintenance, preparing your heirs, retirement issues faced by women, the threat of elder financial abuse, going beyond financials to think about your happiness, and much more. These topics are explained with the help of specialists in each subject. And everything is based on the "science of investing" - evidenced with studies from peer-reviewed journals. Overall, this adds up to a complete retirement guide, packed with the latest and best knowledge. Don't plan your retirement without it."--P. 4 of cover.
Keywords: Grogan, Kevin, -- 1983-; Retirement -- Planning; Investments; Retirement income -- United States -- Planning; Older people -- Finance, Personal